PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING - Aulia Nur Fadiyanti; Fitri Lukiastuti; Pandji Anoraga (Magister Manajemen STIE Bank BPD Jateng, 2017)
This study aims to examine and analyze whether there is influence of job satisfaction on turnover intention of employees with organizational commitment as an intervening variable. Objects that are examined in this study is KJKS BMT Bina Ummat Sejahtera Cabang Tegal. The sample in this study were all employees KJKS BMT Bina Ummat Sejahtera Cabang Tegal totaling 49 employees that serve as the respondent. The sampling technique in this research is census and data analysis methods used in this research is simple regression test and test indirect effect mediation using bootstrapping (SPSS Macro). The results showed that organizational commitment negatively affect turnover intention with the t test value is -4.794 and the signification is 0.000, job satisfaction has positive influence on organizational commitment with the t test value is 2.587 and the signification is 0.013, and job satisfaction effect on turnover intention through organizational commitment with the t test value is 2.993.